قياس وتحليل محددات الادخار المحلي في العراق للمدة (2004-2019) - غفور, أ.م.د.نرمين معروف; قادر, جيا صالح (Sulaimani Journal for Humanities, 2023)
Local saving is one of the stimulating elements of economic growth through its potential in financing investment and establishing productive projects, which leads to achieving higher levels of productivity This research aims to measure and analyze the determinants of domestic saving in Iraq during the period (2004-2019) so that it can be focused on in the event of any policy to raise the rate of domestic savings in the future. Based on the hypothesis that recognizes the existence of economic and non-economic factors varying importance and impact in determining the level and percentage of domestic saving, the research relied on the inductive approach to familiarize himself with the theoretical framework related to clarifying what savings is, and the statement of the factors affecting it, in addition to the deductive approach to measure and analyze the determinants of local saving in Iraq during the study period. Several conclusions were reached, including that domestic saving in Iraq in the short and long term is affected and determined by several factors and that there is a moral and positive impact of national income on domestic saving, as well as there is a moral and negative impact of both total consumption, inflation rate and unemployment rate on domestic saving, with a negative moral impact of the interest rate on domestic savings. To achieve the desired goals of domestic savings, the economic authorities should pay attention to reforming fiscal policy as well as developing and reforming the banking system to enhance its role in mobilizing savings deposits and improving their use in the economy.
Keywords: Local savings; the Iraqi economy; determinants of savings; interest rate